PENGARUH KESELAMATAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA CV. TRI MUTIARA KIRANA JAKARTA SELATAN - Indri Septyarini; Zakaria (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine how the Influence of Work Safety and Work Discipline on Employee Performance at CV. Tri Mutiara Kirana South Jakarta. The method used in this study is a quantitative descriptive method. The Sampling Technique used is a saturated sampling technique with a sample of 60 respondents. Data analysis using validity test, reliability test, classical assumption test, linear regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis test. The results of this study are that Safety has a significant effect on Employee Performance with the regression equation Y = 28.138 + 0.347 X1, the correlation coefficient is 0.644, meaning that both variables have a strong relationship with a determination value or contribution of influence of 0.360 or 36% while the remaining 64% is influenced by other factors. Hypothesis testing obtained a calculated t value> t table or (2.919> 1.672). Thus, H0 is rejected and Ha is accepted, meaning that there is a significant influence between Safety on Employee Performance. Discipline has a significant effect on Employee Performance with the regression equation Y = 32.385 + 0.238 X2, the correlation coefficient is 0.680, meaning that both variables have a strong relationship with a determination value or influence contribution of 0.330 or 33% while the remaining 67% is influenced by other factors. Hypothesis testing obtained a calculated t value> t table or (2.396> 1.672). Thus, H0 is rejected and Ha is accepted, meaning that there is a significant influence between Discipline and Employee Performance. Safety and Discipline have a significant effect on Employee Performance with the regression equation Y = 23.654 + 0.295 X1 + 0.349 X2. The correlation coefficient value or the level of relationship between the independent variable and the dependent variable is obtained at 0.767, meaning that it has a strong relationship with a determination coefficient value or simultaneous influence contribution of 0.470 or 47% while the remaining 53% is influenced by other factors. Hypothesis test obtained F count value > F table or (3.319 > 3.16). Thus H0 is rejected and Ha is accepted, meaning there is a significant simultaneous influence between safety and discipline on employee performance at CV. Tri Mutiara Kirana South Jakarta.